Gingival biotype – comparative analysis of different evaluation methods - Djordjević, Filip; Dubovina, Dejan; Bubalo, Marija; Radosavljević, Radivoje; Bukumirić, Zoran (Vojnosanitetski pregled, 2022)
Background/Aim. Gingival biotype can have a significant impact on the outcome of the periodontal therapeutic procedures and the predictability of their aesthetic outcome. There is a strong correlation between the types of biotype and the potential gingival recession after restorative, periodontal, and implant surgical procedures. Therefore, accurate identification of gingival biotypes before initiating these procedures is one of the significant predictive factors for their success. The aim of this study was to evaluate the reliability of accurate gingival biotype determination with the use of the visual method, periodontal, and trans-gingival probing compared to the direct measurement method. Methods. This prospective study involved 33 patients indicated for apical root resection in the intercanine sector of the upper jaw. Gingival biotype identification was performed in all patients using the following techniques: 1) visual method; 2) periodontal probe technique; 3) trans-gingival probing; and 4) direct measurement after flap elevation. Statistical analysis of the obtained data was performed to assess the diagnostic accuracy of the visual method, periodontal probing method, and trans-gingival probing method in relation to the direct measurement method, used as a gold standard, to discriminate the gingival thickness biotype (thin versus thick). Results. The overall accuracy of the tested diagnostic procedures compared to direct gingival biotype measurement was 66.7% for the visual method, 78.8% for periodontal probing, and 97.0% for trans-mucosal probing. Conclusion. The periodontal probing method can be recommended for gingival biotype determination as a routine method since its sensitivity and overall accuracy are higher compared to the visual method. The trans-gingival method, in terms of sensitivity and comprehensive accuracy, almost completely coincides with the direct method, but it is more invasive compared to the periodontal probing method, and it has to be conducted in local anesthesia.
Keywords: evaluation study; gingiva; methods; periodontium; phenotype; surgery, oral.